Integrating Advanced Practice Registered Nurses Into Nursing Homes. Issue 2 (April 2015) - Vogelsmeier, Amy; Popejoy, Lori; Rantz, Marilyn; Flesner, Marcia; Lueckenotte, Annette; Alexander, Greg
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is Available in the Text.